Towards a national adaptation strategy in view of climate changes - DOUKAKIS, E. (Mediterranean Marine Science, 2004)
The continuously increasing emissions of CO2 and Methane result in the enhanced greenhouse effect. The IPCC assessments for the 21st century refer to a 3oC increase in temperature and 50 cm rise in sea level on average. It is therefore understood that every nation must create a National Adaptation Strategy to face the impacts of the forthcoming climate changes. For Greece, an adaptation plan should include: The vulnerability index of the coastal regions according to the national development plan. The determination of the procedures towards adaptation in view of climate changes. The determination of the national criteria to face extreme phenomena due to anthropogenic climate changes. The technical and legal action plans. The responsibility of the various public sectors to overcome gaps or overlaps in the actions to mitigate the impact and The general national adaptation principles. The presentation analyses all the above concepts and proposes specific guidelines to formulate a Greek National Adaptation Strategy to mitigate the impacts of anthropogenic climate changes.